Locoregional Therapies for the Treatment of Hepatic Metastases from Breast and Gynecologic Cancers - Mouli, Samdeep K.; Gupta, Ramona; Sheth, Neil; Gordon, Andrew C.; Lewandowski, Robert J. (Seminars in Interventional Radiology, 2018)
Breast cancer is the most common women's malignancy in the United States and is the second leading cause of cancer death. More than half of patients with breast cancer will develop hepatic metastases; this portends a poorer prognosis. In the appropriately selected patient, there does appear to be a role for curative (surgery, ablation) or palliative (intra-arterial treatments) locoregional therapy. Gynecologic malignancies are less common and metastases to the liver are most often seen in the setting of disseminated disease. The role of locoregional therapies in these patients is not well reported. The purpose of this article is to review the outcomes data of locoregional therapies in the treatment of hepatic metastases from breast and gynecologic malignancies.
Keywords: breast cancer; gynecologic malignancies; liver metastases; chemoembolization; radioembolization; interventional radiology